Transteoretik model temelli geliştirilen ''hadi hareket et'' (hahet) mobil yazılım programının üniversite öğrencilerinin sedanter yaşam davranışlarına etkisi - Özdemir, Gözde (My University, 2025)
Amaç: Transteoretik Model (TTM) temelli 'Hadi Hareket Et' (HaHEt) mobil yazılım programını geliştirmek ve programın üniversite öğrencilerinin sedanter yaşam davranışlarını değiştirmedeki etkisinin incelenmesidir. Gereç ve Yöntem: Araştırma, bir vakıf üniversitesinde, randomize kontrollü deneysel tasarım ile 194 öğrenci (97 deney, 97 kontrol) ile yürütüldü. Deney grubuna TTM temelli HaHEt mobil hafta uygulandı. Veriler, HaHEt uygulaması üzerinden TTM ölçekleri, Uluslararası Fiziksel Aktivite Anketi (UAFAA) ve adım sayısı ön-son ve izlem testte toplandı. Antropometrik ölçümler araştırmacı tarafından ölçüldü. Veriler, grup içi Paired-Sample t testi/ Wilcoxon ve Repeated-measures ANOVA/ Friedman testi, gruplar arası Independent Sample t testi/ Mann-Whitney U ve One-way ANOVA/ Kruskal-Wallis testi, kategorik değişkenler için Ki-kare/ Fisher testi ile analiz edildi. Anlamlılık düzeyi p<0,05’tir. Bulgular: UAFAA toplam MET puanı deney grubunda kontrol grubuna göre son testte 2271,41 puan arttı ve izlem testinde bu artış korundu (p<0,05). Deney grubunda kas oranı başlangıca göre son test ve izlem testinde anlamlı olarak yükselmiş, yağ oranı ise başlangıca göre son test ve izlem testinde anlamlı olarak düşmüştür (p<0,05). Günlük ortalama adım sayısı deney grubunda kontrol grubuna göre son ve izlem testte anlamlı olarak arttı (p<0,05). Araştırmanın sonunda deney ve kontrol grupları arasında TTM ölçek puanları (değişim aşamaları, öz-etkililik ve yarar-zarar algısı) ve BKİ kategorileri anlamlı fark bulunmadı (p>0,05). Sonuç: HaHEt programının, üniversite öğrencilerinin fiziksel aktivite düzeylerini artırmada ve vücut kompozisyonunu iyileştirmede etkili olduğu belirlendi. Ancak, TTM'nin değişkenlerinde istenen değişim için daha uzun müdahaleler gereklidir.

Objectice: The aim of the study is to develop the Transtheoretical Model (TTM) based 'Let's Move' (HaHEt) mobile software program and to examine the effect of the program on changing the sedentary behaviors of university students. Materials and Methods: The study was conducted with 194 students (97 experimental, 97 control) in a foundation university with a randomized controlled experimental design. The TTM-based HaHEt mobile program was applied to the experimental group for 12 weeks. Data were collected from the HaHEt application using the TTM scales, International Physical Activity Questionnaire (IPAQ) and step count in pre-post and follow-up tests. Anthropometric measurements were measured by the researcher. Data were analyzed with the intra-group Paired-Sample t test/ Wilcoxon and Repeated-measures ANOVA/ Friedman test, between-group Independent Sample t test/ Mann-Whitney U and One-way ANOVA/ Kruskal-Wallis test, and for categorical variables, the Chi-square/ Fisher test. The significance level is p<0.05. Results: IPAQ total MET score increased by 2271,41 points in the experimental group compared to the control group in the post-test and this increase was maintained in the follow-up test (p<0,05). In the experimental group, muscle ratio increased significantly in the post-test and follow-up tests compared to the baseline, while fat ratio decreased significantly in the post-test and follow-up tests compared to the baseline (p<0,05). The average daily step count increased significantly in the experimental group compared to the control group in the post-test and follow-up tests (p<0,05). At the end of the study, no significant difference was found between the experimental and control groups in terms of TTM scale scores (stages of change, self-efficacy and benefit-harm perception) and BMI categories (p>0,05). Conclusion: The HaHEt program was found to be effective in increasing the physical activity levels of university students and improving body composition. However, longer interventions are required for the desired change in the variables of TTM.
The effect of the mobile software ''let's move'' (LM) program on changing sedentary behaviors of university students
Keywords: Behavioral Change; Davranış Değişimi TTM; Fiziksel Aktivite; Halk sağlığı hemşireliği; Mobil Uygulama; Mobile Application; Physical Activity; Public health nursing; Sedanter Davranış; Sedentary Behavior; TTM; University Students; Üniversite Öğrencileri